2017
DOI: 10.1038/s41598-017-12691-y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Kinetics of Integrin Receptor Binding to Hepatic Extracellular Matrix Proteins

Abstract: The composition of the extracellular matrix (ECM) proteins and the expression of their cognate receptors dictate cell behavior and dynamics. In particular, the interactions of ECM proteins with integrin receptors are key mediators of these cellular processes, playing a crucial role in the progression of several diseases of the liver, including inflammation, fibrosis/cirrhosis and cancer. This study establishes a modeling approach combining computation and experiments to evaluate the kinetics of integrin recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…While integrin αv is expressed by parenchymal cells and HSCs, most integrin β3 was expressed on HSCs [ 29 ]. Furthermore, while integrin αv forms complexes with several β subunits (β1, β3, β5, β6, β8), integrin β3 forms complexes with only two type α subunits, αv and αIIb [ 30 ]. It might be thought that amount of integrin αvβ3 is similar to integrin β3 rather than integrin αv.…”
Section: Discussionmentioning
confidence: 99%
“…While integrin αv is expressed by parenchymal cells and HSCs, most integrin β3 was expressed on HSCs [ 29 ]. Furthermore, while integrin αv forms complexes with several β subunits (β1, β3, β5, β6, β8), integrin β3 forms complexes with only two type α subunits, αv and αIIb [ 30 ]. It might be thought that amount of integrin αvβ3 is similar to integrin β3 rather than integrin αv.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated a similar concept by modelling the effect of ECM concentration and composition upon the kinetics of integrin binding and clustering (Hudson et al, ). In the same way, the concentration‐dependent dynamics and substrate specificity of RTK signalling in response to changing ECM conditions are key computational parameters required for future model development.…”
Section: Potential Applications For Modelling Of Matrix Signallingmentioning
confidence: 99%
“…Previous modeling has evaluated growth of liver metastases 1012 , development of liver fibrosis 13,14 , and treatment of liver metastases via nanotherapy 15,16 . Recently, the kinetics of integrin receptor binding to hepatic ECM proteins were modeled 17 . However, the interaction of liver metastases, ECM and tumor-associated macrophages has not been extensively evaluated in a unified modeling framework.…”
Section: Introductionmentioning
confidence: 99%